The Influence Of Customer Intimacy, Perceived Usefulness, And Perceived Ease Of Use On Customer Satisfaction In Using Bank Aceh Mobile Banking - Azura, Maya; Amri; Syahrizal, Teuku Muhammad (JIMEBIS: Scientific Journal of Students Islamic Economics and Business, 2026)
The purpose of this study is to examine how customer satisfaction with the Mobile Banking Action Bank Aceh application is influenced by customer intimacy, perceived usefulness, and perceived ease of use. 114 respondents who use the Mobile Banking Action Bank Aceh were given questionnaires as part of this study's quantitative survey method. Purposive sampling is the sampling strategy employed, and SPSS version 25 is used to analyze the data using multiple linear regression. The findings demonstrate that customer satisfaction is not significantly impacted by perceived usefulness or customer intimacy. Customer satisfaction, on the other hand, is positively and significantly impacted by perceived ease of use, meaning that the more user-friendly an application is, the more satisfied customers are. Customer intimacy, perceived usefulness, and perceived ease of use all have a substantial simultaneous impact on customer satisfaction. These results show that the most important factor influencing user satisfaction when using the Mobile Banking Action Bank Aceh service is ease of use. Therefore, the bank should continue to prioritize increasing accessibility and user experience in order to raise and sustain customer satisfaction levels.